India - Uttarakhand Economic Assessment - World Bank (Washington, DC, 2013)
In 2010, Uttarakhand entered the second decade of its existence as a separate State. During the first decade, average individual incomes rose by eight ranks in relation to the other States in India. Although these incomes are still below the median for India, they are growing significantly faster, which is leading to rapid convergence with the richer States. Looking ahead, the State can build upon its existing growth momentum, the economic diversification that has resulted from its industrial promotion policies, its favorable location in the dynamic North Indian economy, and good natural resources and skills bases to raise standards of living. This report intends to provide inputs for development thinking that is underway during the Twelfth Five-Year Plan period. It covers the subjects of growth, inclusion, sustainability, public finance and administration, responding to the Government s request for a discussion of these areas. It attempts to strike a balance between broad-brushed strategies and specific and practical recommendations, bringing to bear experience from other States and countries when needed. The overall message to policymakers is: Over the next decade, Uttarakhand should aim to become the preferred State in North India for (a) investing in the production of high value goods and in services; (b) livability; (c) greening; and (d) good government. The global community, including India s multilateral and bilateral development partners can be rich sources of knowledge about design, funds, and implementation support for the State Government s development program. Early actions to engage a wide variety of development partners is likely to help Uttarakhand effectively and efficiently traverse a challenging and unique development path.